PENGARUH PENDIDIKAN TERHADAP KEBERHASILAN PEKERJA MIGRAN SEKTOR INFORMAL DI KOTA PALEMBANG - Dessy Hersahanty (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
The phenomenon of migrants invading the big city is apparently inseparable from the growth of the informal sector. The informal sector occurs when the city is limited to provide adequate employment. Very limited job opportunities in the formal sector make the informal sector an alternative destination for migrants to survive. This study looks at the effect of education on the success of informal sector migrant workers in the city of Palembang. This study uses a simple linear regression analysis with the results that show that Education influences the success of informal sector migrant workers in Palembang City.